COPART Risk Score Predicts Long-term Mortality in Peripheral Arterial Occlusive Disease. Issue 1 (July 2015) - Hackl, G.; Belaj, K.; Gary, T.; Rief, P.; Deutschmann, H.; Seinost, G.; Brodmann, M.; Hafner, F.
Abstract : Objectives: The COhorte de Patients ARTériopathes (COPART) Risk Score is a risk score assessing the 1 year outcome of patients who received inpatient treatment because of their peripheral arterial occlusive disease (PAOD). The COPART Risk Score consists of six variables each of which is allocated a different number of points (age, history of myocardial infarction, C-reactive protein, ankle–brachial index, estimated glomerular filtration rate, medication with antiplatelet agents, statins and renin–angiotensin system inhibitors). Methods: 129 consecutive claudicants were included in a prospective trial with an average follow up of 8.8 (± 0.7) years. All patients were hospitalized for their first endovascular procedure to the pelvic and/or femoropopliteal arteries. The endpoints were all cause mortality and cardiovascular (CV) death. The COPART Risk Score was calculated for the three patient cohorts (low risk: 52 patients [40.3%]; medium risk: 41 patients [31.8%]; high risk: 36 patients [27.9%]). Results: During the follow up period 23.1% ( n = 12) of patients in the low risk group, 34.1% ( n = 14) of patients in the medium risk group, and 63.9% ( n = 23) of patients in the high risk group died. CV death occurred in 11.5% in the low, 22.0% in the medium, and 41.7% in the high risk groups. The three groups differed significantly with regard to all cause and CV mortality ( p < .0001 and p = .001). Conclusions: The COPART Risk Score is a suitable instrument to predict long-term all cause and CV mortality in claudicants preceding their first peripheral intervention.